(untitled) (Sustainability in Debate, 2012)
To contribute to the debate around the role of the programs of Payment for Environmental Services (PES) for sustainable development, this work has as main objective to identify the potential of PES as an instrument of public policy for sustainable development of rural territories. The paper presents a brief theoretical review of PES, the main features of some programs Brazilian PES and presentation and prospects of the project “Protetor das Águas”, which has been running in the city of Vera Cruz-RS, with the aim of contributing to the protection of sources of sub-basin of the Arroio Andreas, rewarding family farmers. Despite the very early stage, the expectations of the project are very optimistic, because most of the family owners of the sub-basin have shown interest in participating in the project. The PES programs contribute to the sustainable development of rural territories because they open space for the formation and expansion of productive systems agroecological and tourism, generating income and employment opportunities in these territories